2017
DOI: 10.18632/oncotarget.16241
|View full text |Cite
|
Sign up to set email alerts
|

Possible benefits from post-mastectomy radiotherapy in node-negative breast cancer patients: a multicenter analysis in Korea (KROG 14-22)

Abstract: PurposeThis study was performed to identify a subset of patients who may benefit from post-mastectomy radiotherapy (PMRT) among node-negative breast cancer patients.Materials and MethodsWe retrospectively reviewed 1,828 patients with pT1-2N0 breast cancer, treated with mastectomy without PMRT from 2005 to 2010 at 10 institutions. Univariate and multivariate analyses for locoregional recurrence (LRR) and any first recurrence (AFR) were performed according to clinicopathologic factors and biologic subtypes.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Other research demonstrated that post-MAS radiotherapy (PMRT) has a strong potential to produce a positive prognosis in females with stage T3-T4 breast cancer, or those where the cancer has spread to four or more positive axillary lymph nodes (LNs) (10,11). Furthermore, a large retrospective study indicated that patients with node-negative breast cancer may also benefit from PMRT (12). However, the use of PMRT to improve breast cancer-specific survival (BCSS) and OS rates in early-stage (T1-2) breast cancer, and those with one to three positive axillary LNs, is controversial (13), due to limited clarity in the current evidence and a lack of data from large, high-quality clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other research demonstrated that post-MAS radiotherapy (PMRT) has a strong potential to produce a positive prognosis in females with stage T3-T4 breast cancer, or those where the cancer has spread to four or more positive axillary lymph nodes (LNs) (10,11). Furthermore, a large retrospective study indicated that patients with node-negative breast cancer may also benefit from PMRT (12). However, the use of PMRT to improve breast cancer-specific survival (BCSS) and OS rates in early-stage (T1-2) breast cancer, and those with one to three positive axillary LNs, is controversial (13), due to limited clarity in the current evidence and a lack of data from large, high-quality clinical studies.…”
Section: Introductionmentioning
confidence: 99%